PENGARUH KEPEMILIKAN MANAJERIAL DAN KOMPENSASI EKSEKUTIF TERHADAP PENGHINDARAN PAJAK DENGAN KUALITAS AUDIT SEBAGAI VARIABEL PEMODERASI - Regina (2021)
This study aims to determine the effect of managerial ownership and executive compensation on tax avoidance with audit quality as a moderating variable on listed manufacturing companies in the Indonesian Stock Exchange 2017-2019. This research uses quantitative research methods with secondary data form annual reports. This study has a sample of 47 manufacturing companies. The data analysis technique that used are the regression model selection test, classic assumption test, multiple regression and hypothesis testing (t test). Based on the results of data analysis, it can be concluded that (1) managerial ownership has no effect on tax avoidance, (2) executive compensation has a significant positive effect on tax avoidance, (3) audit quality strengthens the effect of managerial ownership on tax avoidance, and (4) audit quality cannot moderate the effect of executive compensation on tax avoidance